ANALYSIS OF HEALTH PROMOTION MEDIA MANAGEMENT IN THE KIA POLYCLINIC AT THE BLUD UPTD JATI RAYA COMMUNITY HEALTH CENTER, KENDARI CITY IN 2025 - Nur Amal Sasmita; Hartati Bahar; Kamrin Kamrin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
The KIA (Motherhood and Child Health) Clinic is the spearhead of health services because it is the primary place for interaction between pregnant women and health workers, both for examinations, education, and counseling. Therefore, health promotion media needs to be managed in a planned manner to optimally convey messages. This study aims to analyze the management of health promotion media in the KIA Clinic using a descriptive qualitative method. Six informants were selected through purposive sampling, consisting of health promotion officers, heads of community health centers, KIA clinic officers, and patients. Data collection was conducted through observation, in-depth interviews, recording, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results showed that health promotion media management has been running quite well. The product aspect includes the use of leaflets, posters, and flipcharts in accordance with guidelines, but is still dominated by print media. The price aspect is relatively affordable, although budget constraints affect media variation. The place aspect is considered strategic through placement in waiting rooms and direct distribution and utilization of integrated health posts (Posyandu) and social media. The promotion aspect is carried out through lectures, counseling, and questions and answers, although obstacles still exist. In conclusion, health promotion media management is quite effective, but requires optimization of digital media and innovation in outreach strategies.